Evaluation Of Tourism Object Development Of Bukit Kandis In Central Bengkulu Regency - Yusuarsono, Yusuarsono; Kader, Bando Amin C.; Agustina, Elisa (Utan Kayu Publishing, 2021)
This study aims to evaluate the development of Bukit Kandis tourist destination located in Durian Demang Village, Central Bengkulu Regency. The evaluation focuses on three main aspects: infrastructure, socio-economic impact on the local community, and environmental-cultural sustainability. A qualitative descriptive method was applied, with data collected through in-depth interviews, observation, and documentation involving members of the tourism awareness group (Pokdarwis) and surrounding residents. The findings reveal that the development of Bukit Kandis tourism site has had a positive effect on increasing local income and creating new employment opportunities. Economic activities such as food stalls, parking services, and recreational facility rentals have grown significantly. However, several challenges remain, including inadequate tourism service training, limited supporting infrastructure, and insufficient promotional efforts. Continuous support from the local government and multi-stakeholder collaboration is required to ensure the site's sustainability. The study concludes that community-based participatory management is the key to successful and sustainable rural tourism development.